Analysis of the factors involved in procedural failure: Endoscopic retrograde cholangiopancreatography using a short‐type single‐balloon enteroscope for patients with surgically altered gastrointestinal anatomy. Issue 6 (24th April 2019) - Tanisaka, Yuki; Ryozawa, Shomei; Mizuide, Masafumi; Harada, Maiko; Fujita, Akashi; Ogawa, Tomoya; Nonaka, Kouichi; Tashima, Tomoaki; Araki, Ryuichiro
Abstract : Aim: To analyze factors involved in procedural failure and to discuss responses to procedural failure by using the outcomes of endoscopic retrograde cholangiopancreatography (ERCP) carried out using a short‐type single‐balloon enteroscope (short SBE) in patients with surgically altered gastrointestinal anatomy. Methods: The study sample included patients who underwent ERCP‐related procedures using a short SBE between September 2011 and September 2018 at our hospital. Outcomes, including procedural success rate, were studied retrospectively to analyze the factors involved in procedural failure. Results: Analysis included 191 procedures carried out in 121 patients. Procedural success rate was 85.9% with an adverse event rate of 8.4%. Causes of procedural failure included malignant biliary obstruction (odds ratio [OR] 2.89, 95% confidence interval [CI] 1.19–7.25, P = 0.02), first ERCP attempt (OR: 5.32, 95% CI: 1.30–36.30, P = 0.02), and Roux‐en‐Y reconstruction (OR: 0.08, 95% CI: 0.004–0.39, P < 0.001). With regard to the response to failure, in cases of malignant biliary obstruction, reattempted short SBE‐assisted ERCP was difficult because of invasion of the small intestine or papilla. A large number of these cases required alternative treatment (10 of 15 cases, 66.7%) using percutaneous transhepatic biliary drainage (PTBD) or endoscopic ultrasound‐guided biliary drainage (EUS‐BD). Conclusion: Endoscopic retrograde cholangiopancreatography using a short SBE is safe and effective, with malignant biliary obstruction being a specific cause of failure. Technical proficiency with different modalities, such as PTBD and EUS‐BD, is necessary to respond to failure in these cases.